Thin‐Metal‐Film‐Based Transparent Conductors: Material Preparation, Optical Design, and Device Applications. Issue 3 (30th November 2020) - Zhang, Cheng; Ji, Chengang; Park, Yong‐Bum; Guo, L. Jay
Abstract: Transparent conductors are essential elements in an array of optoelectronic devices. The most commonly used transparent conductor – indium tin oxide (ITO) suffers from issues including poor mechanical flexibility, rising cost, and the need for annealing to achieve high conductivity. Consequently, there has been intensive research effort in developing ITO‐free transparent conductors over the recent years. This article gives a comprehensive review on the development of an important ITO‐free transparent conductor, that is based on thin metal films. It starts with the background knowledge of material selection for thin‐metal‐film‐based transparent conductors and then surveys various techniques to fabricate high‐quality thin metal films. Then, it introduces the spectroscopic ellipsometry method for characterizing thin metal films with high accuracy, and discusses the optical design procedure for optimizing transmittance through thin‐metal‐film‐based conductors. The review also summarizes diverse applications of thin‐metal‐film‐based transparent conductors, ranging from solar cells and organic light emitting diodes, to optical spectrum filters, low‐emissivity windows, and transparent electromagnetic interference coatings. Abstract : This review summarizes the recent development of thin‐metal‐film‐based transparent conductors. It starts with the general guidelines of material selection, and then surveys various techniques for preparing and characterizing high‐quality ultrathin metal films. Finally, it discusses relevant optical design procedures for maximizing the conductor's transmittance as well as classical and emerging applications of thin‐metal‐film‐based transparent conductors.